Preparation method and application of Co (at) G / CNT nanorod composite material with ultra-wide electromagnetic wave absorption performance
Through the preparation method of Co@G/CNT nanorod composite material, the technology of hydrothermal synthesis and in-situ growth of carbon nanotubes is used to solve the problems of limited performance and complex preparation of existing electromagnetic wave absorbing materials, and realize the ultra-wide band Efficient electromagnetic wave absorption and simplified production process.
Patent Information
- Application Number
- CN202411535613.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing electromagnetic wave absorbing materials have limited absorption performance in the spectrum range and the production process is complex, resulting in high cost and low production efficiency.
Using the preparation method of Co@G/CNT nanorod composite material, the hydrothermal synthesis of cobalt salt and zinc salt under the action of surfactant CTAB is formed to form a rod-shaped bimetallic organic framework precursor and calcined under a specific hydrogen atmosphere. Induce the growth of carbon nanotubes to form a continuous conductive network.
The ultra-wide electromagnetic wave absorption performance is achieved, especially in the frequency range of 2 to 18GHz, the material's reflection loss reaches -40.36dB, and the effective absorption bandwidth can reach 13.2GHz, which reduces the density of the material and improves production efficiency.
Smart Images

Figure CN119410341A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electromagnetic wave absorption materials, and in particular to a preparation method and application of a Co@G / CNT nanorod composite material with ultra-wide electromagnetic wave absorption performance. Background Art
[0002] Electromagnetic radiation pollution generated by the extensive use of emerging electronic devices, from household appliances to wireless base stations and military radars, poses a serious threat to human health and national defense security. Therefore, the demand for high-performance electromagnetic wave absorbing (EWA) materials is urgent. Magnetic materials, including metals (Co, Ni, Fe) and metal alloys (FeCo, CoNi, etc.), are generally used as microwave absorbers due to their strong magnetic loss capacity. Carbonaceous materials are often used as matrices to support magnetic components due to their light weight, high dielectric loss and low cost, as well as their huge surface area and strong affinity for magnetic particles. The combination of carbon-based materials and magnetic components improves the absorption performance by increasing dielectric loss and improving impedance matching due to the synergistic effect between their dielectric and magnetic components. Usually, researchers generally use multi-component composite materials obtained by combining doped carbon nanotubes with magnetic metals, but their preparation process is complicated. In summary, the combination of carbon-based materials and magnetic metals provides new ideas and methods for the design and development of lightweight and efficient electromagnetic wave absorbing materials. The clever combination will give full play to the respective advantages of both, provide strong support for solving the problems existing in traditional absorbing materials and promote the research and application in the field of electromagnetic wave absorbing materials. Summary of the invention
[0003] In view of the above technical problems existing in the prior art, the purpose of the present application is to provide a Co@G / CNT nanorod composite absorbing material with ultra-wide electromagnetic wave absorption performance and a preparation method and application thereof.
[0004] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0005] The method for preparing the Co@G / CNT nanorod composite material with ultra-wide electromagnetic wave absorption performance comprises the following steps:
[0006] 1) Dissolve Co(CH3COO)2·4H2O and Zn(CH3COO)2·2H2O in ultrapure water to prepare solution a;
[0007] 2) dimethylimidazole and CTAB are mixed and dissolved in ultrapure water to obtain solution b;
[0008] 3) Rapidly add solution a to solution b, stir at room temperature, transfer the mixed solution to a stainless steel reactor with a Teflon lining and perform a hydrothermal reaction at 100-140° C. for 24-50 hours. After the reaction is completed, cool to room temperature, centrifuge, wash, and dry to obtain a CoZn-ZIF precursor;
[0009] 4) The CoZn-ZIF precursor is calcined in an Ar / H2 atmosphere to obtain a Co@G / CNT nanorod composite material with ultra-wide electromagnetic wave absorption performance.
[0010] Furthermore, in step 1), the molar ratio of Co(CH3COO)2·4H2O to Zn(CH3COO)2·2H2O is 1:1-5, preferably 1:2-3.
[0011] Furthermore, in step 2), the mass of CTAB is 2-10%, preferably 4-6%, of the mass of dimethylimidazole.
[0012] Furthermore, the ratio of the total amount of Co(CH3COO)2·4H2O and Zn(CH3COO)2·2H2O in step 1) to the mass of dimethylimidazole in step 2) is 1:2-5, preferably 1:2.5-3.
[0013] Furthermore, in step 3), the dispersion concentration of dimethylimidazole in the mixed solution is 40-200 mg / mL, preferably 70-80 mg / mL.
[0014] Furthermore, in step 3), the temperature of the hydrothermal reaction is 110-120° C., and the reaction time is 40-48 h.
[0015] Furthermore, in step 4), the volume fraction of H2 in the Ar / H2 atmosphere is 2-10%, preferably 5-6%; step 4) calcination is carried out in two steps, the first step of calcination is calcination at 300-400°C for 1-2h, and the second step of calcination is calcination at 700-900°C for 2-5h.
[0016] Furthermore, the temperature of the first calcination step is 350° C. and the calcination time is 1.5-2 h, and the temperature of the second calcination step is 800° C. and the calcination time is 3-4 h.
[0017] The invention discloses an application of a Co@G / CNT nanorod composite material with ultra-wide electromagnetic wave absorption performance, wherein the material is used for absorbing electromagnetic waves within a frequency range of 2 to 18 GHz.
[0018] The present application discloses a Co@G / CNT nanorod composite absorbing material with ultra-wide electromagnetic wave absorption performance. Through a simple synthesis strategy, the synthesis mechanism of the absorbing material is: cobalt salt and zinc salt are hydrothermally synthesized under the action of surfactant CTAB to obtain a rod-shaped bimetallic organic framework precursor; due to the catalytic effect of Co metal, carbon nanotubes can be directly induced to grow on the carbon rod substrate under a specific hydrogen atmosphere. This in-situ growth method avoids complex mixing, dispersion and subsequent processing steps, greatly simplifies the preparation process, improves production efficiency and reduces production costs. Carbon nanotubes can form a continuous conductive network, which is conducive to adjusting the electromagnetic parameters of the material, such as dielectric constant and magnetic permeability, and is conducive to improving impedance matching, thereby achieving effective absorption in a wider frequency band. In addition, the magnetic metal that catalyzes the carbon nanotubes provides magnetic loss, and the good mutual synergistic effect of magnetic loss and dielectric loss can further improve the absorbing performance. The present invention uses ultrapure water as a solvent, has a simple preparation process, is relatively energy-saving and environmentally friendly, and the drugs used are low in price, and can achieve large-scale production.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] 1) The present invention prepares a Co@G / CNT nanorod composite absorbing material with ultra-wide electromagnetic wave absorption performance by in-situ growth of carbon nanotubes, so that the number of carbon nanotubes can be controlled and distributed on the carbon rod substrate, and the material is easy to sublimate at high temperature by zinc to produce a large number of uniform holes, thereby reducing the density of the material, and the magnetic metal cobalt that generates the carbon nanotubes provides magnetic loss. The carbon nanotubes can form a continuous conductive network, which is conducive to adjusting the electromagnetic parameters of the material, such as dielectric constant and magnetic permeability, thereby achieving effective absorption in a wider frequency band. The present invention uses water as a solvent, has a simple preparation process, is relatively energy-saving and environmentally friendly, and the drugs used are low in price and have good absorption performance.
[0021] 2) In the method of in-situ growth of carbon nanotubes, the Co@G / CNT nanorod composite absorbing material with ultra-wide electromagnetic wave absorption performance is prepared by the present invention, by adjusting the Co 2+ and Zn 2+ ions, thereby rationally controlling the content and distribution of Co NPs in Co@G / CNT composites. Zn atoms can effectively block adjacent Co atoms, greatly reducing the agglomeration of magnetic metal Co. Co NPs can be evenly distributed inside and on the surface of CoZn nanorods and carbon nanotubes. Good composition control and ingenious structural design give the material enhanced multiple losses, multiple interface polarizations and better impedance matching, with a reflection loss of -40.36dB. A relatively thin thickness of 3.2mm at 15wt% filler loading can achieve a wide bandwidth of 9.6GHz. Its qualified bandwidth can reach 13.2GHz, achieving more than 99.9999% electromagnetic wave absorption.
[0022] 3) In the Co@G / CNT nanorod composite absorbing material with ultra-wide electromagnetic wave absorption performance prepared by the method of in-situ growth of carbon nanotubes prepared by the present invention, the larger surface area will cause multiple reflections and scattering of electromagnetic waves between the nanorods and the carbon nanotubes on the surface, thereby extending the propagation path of the electromagnetic waves and enhancing the attenuation capability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a comparison chart of X-ray electron diffraction (XRD) of Co@G / CNT-1 material, Co@G / CNT-2 material and Co@G / CNT-3 material prepared in Example 1.
[0024] Figure 2 This is a scanning electron microscope (SEM) test result diagram of the Co@G / CNT composite material of Example 1.
[0025] Figure 3 This is a scanning electron microscope (SEM) test result diagram of the Co@G / CNT composite material of Example 2.
[0026] Figure 4 This is a scanning electron microscope (SEM) test result diagram of the Co@G / CNT composite material of Example 3.
[0027] Figure 5 This is a transmission electron microscopy (TEM) test result diagram of the Co@G / CNT composite material of Example 1.
[0028] Figure 6 This is a transmission electron microscopy (TEM) test result diagram of the Co@G / CNT composite material of Example 2.
[0029] Figure 7 This is the transmission electron microscopy (TEM) test result diagram of the Co@G / CNT composite material of Example 3.
[0030] Figure 8 This is the reflection loss (RL) curve of the Co@G / CNT composite material of Example 1.
[0031] Fig. 9 This is the reflection loss (RL) curve of the Co@G / CNT composite material of Example 2.
[0032] Fig.10 This is the reflection loss (RL) curve of the Co@G / CNT composite material of Example 3. DETAILED DESCRIPTION
[0033] The present invention will be further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0034] Example 1
[0035] A Co@G / CNT nanorod composite material with ultra-wide electromagnetic wave absorption performance is prepared by an in-situ growth method, comprising the following steps:
[0036] 1) Disperse 0.249 g Co(CH3COO)2·4H2O (1 mmol) into 4 ml ultrapure water at room temperature and dissolve it completely by ultrasonication. Then add 0.219 g Zn(CH3COO)2·2H2O (1 mmol) and continue ultrasonication until it is completely dissolved. This is marked as solution a.
[0037] 2) Disperse 4.927 g of dimethylimidazole in 60 ml of ultrapure water and dissolve it completely by sonication. Then add 0.241 g of CTAB and continue sonication until it is completely dissolved. The obtained solution is marked as solution b.
[0038] 3) The prepared solution a was quickly added to the solution b, stirred at room temperature for 5 minutes, and the solution was transferred to a Teflon-lined stainless steel container and heated at 120°C for 48 hours to obtain CoZn-MOF. After cooling to room temperature, the purple powder was collected by centrifugation. It was washed several times with methanol and ethanol, dried at 70°C overnight after centrifugation to obtain the CoZn-ZIF precursor;
[0039] 4) After drying, the CoZn-ZIF precursor sample was heated to 350°C in a tube furnace at a heating rate of 2°C / min and calcined for 1.5 h in an Ar / H2 atmosphere with a H2 volume fraction of 5%, and then the furnace temperature was further increased to 800°C and maintained for 3.5 h. A Co@G / CNT nanorod composite material with ultra-wide electromagnetic wave absorption performance was obtained, which was labeled as Co@G / CNT-2.
[0040] The Co@G / CNT-2 composite material prepared in Example 1 was subjected to an X-ray electron diffraction (XRD) test. The test results are shown in FIG. Figure 1 As shown, the XRD pattern of the Co@G / CNT-2 composite material prepared by the present invention matches well with the results of crystallographic data simulation of composite materials synthesized from cobalt zinc salts in different proportions. The materials all have three obvious peaks at 2θ=44.21°, 51.41° and 75.71°, which can correspond to the (111), (200) and (220) planes of Co NPs, respectively, indicating the presence of high-purity cobalt crystals.
[0041] The preparation method of the Co@G / CNT nanorod composite material in step 1) to step 4) of Example 1 is the same, except that the amount of Co(CH3COO)2·4H2O and Zn(CH3COO)2·2H2O is adjusted in step 1) to maintain the total amount of the two materials at 2 mmol.2+ and Zn 2+ The molar ratio of ions changed to 3:1 and 1:3, and the finally prepared absorbing materials were labeled as Co@G / CNT-1 material and Co@G / CNT-3 material, respectively.
[0042] The Co@G / CNT-1 material, Co@G / CNT-2 material and Co@G / CNT-3 material prepared in Example 1 were all subjected to X-ray electron diffraction (XRD) tests. The test results are as follows: Figure 1 As shown, the XRD pattern of the Co@G / CNT nanorod composite material with ultra-wide electromagnetic wave absorption performance prepared by an in-situ growth method of the present invention matches well with the results of crystallographic data simulation, and the material also has a relatively weak and broad peak near 2θ=25.01°, corresponding to the (002) crystal plane of carbon. This is due to the reduction in the content of CoNPs and the decrease in the degree of graphitization of carbon. No diffraction peaks of zinc and zinc oxide are found in the figure, indicating that the presence of zinc is at a very low level or in an amorphous state at this time.
[0043] The scanning electron microscope (SEM) test results of the Co@G / CNT-2 composite material of Example 1 are as follows: Figure 2 As shown, from Figure 2 It can be seen that there is an obvious rod-like structure and the carbon nanotubes are evenly distributed on the carbon rods, which proves the successful synthesis of the Co@G / CNT-2 composite material, which is consistent with the test results of XRD.
[0044] The results of the transmission electron microscopy (TEM) test of the Co@G / CNT-2 material prepared in Example 1 are as follows: Figure 5 As shown, from Figure 5 It can be seen that Co NPs are distributed on the surface and inside of the carbon skeleton of Co@G / CNT-3, and metal nanoparticles are wrapped at the end of each carbon nanotube. These nanoparticles are wrapped by many graphite carbon layers, which are formed by catalytic graphitization of Co NPs during the carbonization process. Carbon nanotubes can form a continuous conductive network, which is conducive to adjusting the electromagnetic parameters of the material, allowing more electromagnetic waves to enter the interior of the absorbing material, thereby enhancing electromagnetic wave absorption.
[0045] The electromagnetic wave absorption performance of the Co@G / CNT-2 material prepared in Example 1 was tested. The sample was mixed with paraffin, and the sample Co@G / CNT-2 accounted for 15wt% in the mixture. After the mixture was fully stirred and dispersed in cyclohexane, it was heated in a water bath to completely evaporate the solvent. The formed solid was pressed into a sheet with a mold and then tested. The reflection loss (RL) curve of the material at a thickness of 1.0 to 5.5 mm and a frequency of 2 to 18 GHz is as shown in Figure 8 Generally speaking, an RL value lower than –10dB means that 90% of the electromagnetic waves are absorbed. Figure 8As shown, when the thickness is 3.0 mm, the RLmin value of the Co@G / CNT-2 material is –41.23 dB, and when the thickness is 2.5 mm, the effective absorption bandwidth (RL value < –10 dB) is 5.20 GHz (9.69 to 14.89 GHz).
[0046] The excellent wave absorption performance of the Co@G / CNT-2 material of the present invention can be attributed to the good synergistic effect of magnetic loss and dielectric loss. In the traditional method, carbon nanotubes are mostly added to the magnetic material matrix. However, this method has the problems of complicated preparation process, high cost and difficulty in accurately regulating the distribution of carbon nanotubes in the composite material, resulting in poor impedance matching. The design of the present invention cleverly utilizes a simple synthesis strategy to directly induce the growth of carbon nanotubes (CNT) on a carbon rod substrate, and achieves effective control of the number and length of generated carbon nanotubes by finely regulating the ratio of cobalt salt to zinc salt, thereby effectively adjusting and optimizing the wave absorption performance of the material. Compared with the traditional doping method, this in-situ growth method avoids complex mixing, dispersion and subsequent processing steps, greatly simplifies the preparation process, improves production efficiency and reduces production costs. CNT can form a continuous conductive network, which not only enhances the electromagnetic shielding performance of the material, but also helps to adjust the electromagnetic parameters of the material, such as dielectric constant and magnetic permeability, so as to achieve effective wave absorption in a wider frequency band. In addition, the magnetic metal that catalyzes the carbon nanotubes provides magnetic loss. This additional characteristic complements the enhanced dielectric loss to form a dual loss mechanism, which can further improve the wave absorption performance. Therefore, the present invention provides a new design idea and technical support for the preparation of broadband electromagnetic wave absorption materials.
[0047] The Co@G / CNT-2 nanorod composite material with ultra-wide electromagnetic wave absorption performance prepared by the present invention is tested by mixing the sample Co@G / CNT-2 with paraffin to make a ring. When the sample Co@G / CNT-2 accounts for 15wt%, it has good wave absorption performance, which reduces the filling amount of the material and achieves the goal of "lightness". By controlling the proportion of metal salts, a method of preparing a Co@G / CNT nanorod composite material with ultra-wide electromagnetic wave absorption performance by an in-situ growth method is achieved. The present invention uses water as a solvent, the preparation process is simple and environmentally friendly, and the drugs used are inexpensive.
[0048] Example 2
[0049] A Co@G / CNT nanorod composite material with ultra-wide electromagnetic wave absorption performance is prepared by an in-situ growth method at room temperature, comprising the following steps:
[0050] 1) Disperse 0.374 g Co(CH3COO)2·4H2O (1.5 mmol) into 4 ml ultrapure water at room temperature and dissolve it completely by ultrasonication. Then add 0.110 g Zn(CH3COO)2·2H2O (0.5 mmol) and continue ultrasonication until it is completely dissolved. This is marked as solution a.
[0051] 2) Disperse 4.927 g of dimethylimidazole in 60 ml of ultrapure water and dissolve it completely by sonication. Then add 0.241 g of CTAB and continue sonication until it is completely dissolved. The obtained solution is marked as solution b.
[0052] 3) The prepared solution a was quickly added to the solution b, stirred at room temperature for 5 minutes, and the solution was transferred to a Teflon-lined stainless steel container and heated at 120°C for 48 hours to obtain CoZn-MOF. After cooling to room temperature, the purple powder was collected by centrifugation. It was washed several times with methanol and ethanol, dried at 70°C overnight after centrifugation to obtain the CoZn-ZIF precursor;
[0053] 4) After drying, the CoZn-ZIF precursor sample was heated to 350°C in a tube furnace at a heating rate of 2°C / min for 1.5 h in an Ar / H2 atmosphere with a H2 volume fraction of 5%, and then the furnace temperature was further increased to 800°C for 3.5 h. A Co@G / CNT nanorod composite material with ultra-wide electromagnetic wave absorption performance was obtained, which was labeled as Co@G / CNT-1.
[0054] The scanning electron microscopy (SEM) and transmission electron microscopy (TEM) test results of the Co@G / CNT-1 material prepared in Example 2 are as follows: Figure 3 and Figure 6 As shown, from Figure 6 It can be seen that Co NPs are severely agglomerated on the surface and inside the carbon skeleton.
[0055] The electromagnetic wave absorption performance of the Co@G / CNT-1 material prepared in Example 2 was tested. The sample was mixed with paraffin and the test conditions were the same as those in Example 1. The reflection loss (RL) curve of the material at a thickness of 1.0 to 5.5 mm and a frequency of 2 to 18 GHz was as follows: Fig. 9 When the thickness is 2.5 mm, it shows good electromagnetic wave absorption ability and the best RL min The value is –30.23dB, and the corresponding effective absorption bandwidth has a maximum bandwidth of 5.04GHz (12.96~18.0GHz) when the thickness is 2.0mm.
[0056] Compared with Example 1, the absorbing performance of the absorbing material synthesized in Example 2 is reduced. This is because the amount of zinc salt added is less than that in Example 1, which greatly increases the agglomeration of the magnetic metal Co, is not conducive to obtaining good impedance matching, and the Co@G / CNT-1 composite material has poor absorbing performance.
[0057] Example 3
[0058] A Co@G / CNT nanorod composite material with ultra-wide electromagnetic wave absorption performance is prepared by an in-situ growth method at room temperature, comprising the following steps:
[0059] 1) Disperse 0.125 g Co(CH3COO)2·4H2O (0.5 mmol) into 4 ml ultrapure water at room temperature and dissolve it completely by ultrasonication. Then add 0.329 g Zn(CH3COO)2·2H2O (1.5 mmol) and continue ultrasonication until it is completely dissolved. This is marked as solution a.
[0060] 2) Disperse 4.927 g of dimethylimidazole in 60 ml of ultrapure water and dissolve it completely by sonication. Then add 0.241 g of CTAB and continue sonication until it is completely dissolved. The obtained solution is marked as solution b.
[0061] 3) The prepared solution a was quickly added to the solution b, stirred at room temperature for 5 minutes, and the solution was transferred to a Teflon-lined stainless steel container and heated at 120°C for 48 hours to obtain CoZn-MOF. After cooling to room temperature, the purple powder was collected by centrifugation. It was washed several times with methanol and ethanol, dried at 70°C overnight after centrifugation to obtain the CoZn-ZIF precursor;
[0062] 4) After drying, the CoZn-ZIF precursor sample was heated to 350°C in a tube furnace at a heating rate of 2°C / min and calcined for 1.5 h in an Ar / H2 atmosphere with a H2 volume fraction of 5%, and then the furnace temperature was further increased to 800°C and maintained for 3.5 h. A Co@G / CNT nanorod composite material with ultra-wide electromagnetic wave absorption performance was obtained, which was labeled as Co@G / CNT-3.
[0063] The scanning electron microscopy (SEM) and transmission electron microscopy (TEM) test results of the Co@G / CNT-3 material prepared in Example 3 are as follows: Figure 4 and Figure 7 As shown, from Figure 7 It can be seen that Co NPs are more evenly distributed on the surface and inside the carbon skeleton of Co@G / CNT-3.
[0064] The electromagnetic wave absorption performance of the Co@G / CNT-3 material prepared in Example 3 was tested. The sample was mixed with paraffin and the test conditions were the same as those in Example 1. The reflection loss (RL) curve of the material at a thickness of 1.0 to 5.5 mm and a frequency of 2 to 18 GHz was as follows: Fig.10 As shown. When the thickness is 3.0mm, it shows excellent electromagnetic wave absorption ability and the best RL min The value is –40.36dB, and the corresponding effective absorption bandwidth reaches the maximum bandwidth of 9.61GHz (8.39~18.0GHz).
[0065] Compared with Example 1, the absorbing material synthesized in Example 3 has improved absorbing performance. This is because the amount of zinc salt added is greater than that in Example 1, which greatly reduces the agglomeration of the magnetic metal Co and enables the Co NPs to be evenly distributed, thereby increasing the porosity of the material and facilitating good impedance matching. Good component control and ingenious structural design give the Co@G / CNT-3 composite material better absorbing performance.
[0066] Comparative Example 1:
[0067] The preparation steps of the material of Control Example 1 were repeated in Example 1, with the only difference being that "the calcination atmosphere in step 4) was replaced with N2", and the other conditions remained unchanged, and finally a CoZn-ZIF composite material was obtained.
[0068] Comparative Example 1 CoZn-ZIF composite material was tested for electromagnetic wave absorption performance. The sample was mixed with paraffin and the test conditions were the same as those in Example 1. When the thickness was 3.0 mm, the best RL min The value is –24.02dB, and the effective absorption bandwidth (RL value < –10dB) is 2.80GHz (8.87~11.67GHz). Because the magnetic metal Co cannot produce more carbon nanotubes in the N2 atmosphere, the reduction of carbon nanotubes makes it impossible to form a conductive network on the surface, and the conductive loss is reduced; the surface defects are reduced and the attenuation ability is weakened, which ultimately leads to the poor absorption performance of the material.
[0069] The contents described in this specification are merely an enumeration of implementation forms of the inventive concept, and the protection scope of the present invention should not be regarded as being limited to the specific forms described in the embodiments.
Claims
1. A method for preparing a Co@G / CNT nanorod composite material with ultra-wide electromagnetic wave absorption performance, characterized in that The following steps are involved: 1) Dissolve Co(CH3COO)2·4H2O and Zn(CH3COO)2·2H2O in ultrapure water to prepare solution a; 2) Mix and dissolve dimethylimidazole and CTAB in ultrapure water to obtain solution b; 3) Solution a was quickly added to solution b, stirred at room temperature, and the mixture was transferred to a stainless steel reactor with a Teflon lining for hydrothermal reaction at 100-140°C for 24-50h. After the reaction, the mixture was cooled to room temperature, centrifuged, washed, and dried to obtain a CoZn-ZIF precursor; 4) The CoZn-ZIF precursor is calcined in an Ar / H2 atmosphere to obtain a Co@G / CNT nanorod composite material with ultra-wide electromagnetic wave absorption performance.
2. The method for preparing a Co@G / CNT nanorod composite material having ultra-wide electromagnetic wave absorption performance according to claim 1, characterized in that In step 1), the molar ratio of Co(CH3COO)2·4H2O to Zn(CH3COO)2·2H2O is 1:1-5, preferably 1:2-3.
3. The method for preparing a Co@G / CNT nanorod composite material having ultra-wide electromagnetic wave absorption performance according to claim 1, characterized in that In step 2), the mass of CTAB is 2-10% of the mass of dimethylimidazole, preferably 4-6%.
4. The method for preparing a Co@G / CNT nanorod composite material having ultra-wide electromagnetic wave absorption performance according to claim 1, characterized in that The ratio of the total amount of Co(CH3COO)2·4H2O and Zn(CH3COO)2·2H2O in step 1) to the mass of dimethylimidazole in step 2) is 1:2-5, preferably 1:2.5-3.
5. The method for preparing a Co@G / CNT nanorod composite material having ultra-wide electromagnetic wave absorption performance according to claim 1, characterized in that Step 3) The dispersion concentration of dimethylimidazole in the mixed solution is 40-200 mg / mL, preferably 70-80 mg / mL.
6. The method for preparing a Co@G / CNT nanorod composite material having ultra-wide electromagnetic wave absorption performance according to claim 1, characterized in that In step 3), the temperature of the hydrothermal reaction is 110-120° C. and the reaction time is 40-48 h.
7. The method for preparing a Co@G / CNT nanorod composite material having ultra-wide electromagnetic wave absorption performance according to claim 1, characterized in that In step 4), the volume fraction of H2 in the Ar / H2 atmosphere is 2-10%, preferably 5-6%; step 4) calcination is carried out in two steps, the first step of calcination is calcination at 300-400°C for 1-2h, and the second step of calcination is calcination at 700-900°C for 2-5h.
8. The method for preparing a Co@G / CNT nanorod composite material having ultra-wide electromagnetic wave absorption performance according to claim 7, characterized in that The first step of calcination has a temperature of 350°C and a calcination time of 1.5-2 hours, and the second step of calcination has a temperature of 800°C and a calcination time of 3-4 hours.
9. A Co@G / CNT nanorod composite material with ultra-wide electromagnetic wave absorption performance prepared by the method according to any one of claims 1 to 8.
10. The use of a Co@G / CNT nanorod composite material with ultra-wide electromagnetic wave absorption performance as claimed in claim 9, characterized in that The material is used for absorbing electromagnetic waves in the frequency range of 2 to 18 GHz.
Citation Information
Patent Citations
MOF-derived carbon-based magnetic nano composite electromagnetic wave absorbing material and preparation method thereof
CN115491177A
Zinc-cobalt bimetallic selenide carbon nanotube composite material and preparation method and application thereof
CN116435491A
Preparation method of highly dispersed CNTs@ZIF one-dimensional linear nanostructured materials and its application
JP6721813B1
Catalyst structure, use thereof and electrochemical device
US20220297102A1